Cryptococcal eosinophilic meningitis in a patient with sarcoidosis. (18th December 2015) - Hadid, Hiba; Nona, Paul; Usman, Muhammad; Paje, David
Abstract : A 51-year-old African-American man with underlying pulmonary, hepatic and splenic sarcoidosis, reported a 3-day history of headache, neck stiffness and photophobia. He was not using medication for chronic sarcoidosis. Physical examination was significant for nuchal rigidity. Lumbar puncture revealed marked eosinophilia in the cerebrospinal fluid, which, on further analysis, demonstrated a positive cryptococcal antigen. HIV antibody and PCR tests were negative. Bronchoscopy and fungal blood cultures were also negative. The patient was started on amphotericin B and flucytosine, with significant clinical improvement. He recovered well without any neurological sequelae and remained symptom-free at 2-week follow-up. Cryptococcal central nervous infections are uniformly fatal if left untreated. Prompt diagnosis and treatment is essential, to prevent the associated high morbidity and mortality.